Car Loadings As an Index of Trade Volumes - Persons, Warren M. (The Review of Economics and Statistics, 1926)
time trend, reflect the physical volumes of trade and manufacture of the United States. Such figures for total loadings for i919-August I926 are presented in Table 3, and graphically in the lower part of Chart i. The adjusted index of total loadings this year, like indexes of general business and manufacturing activity, though fluctuating at a high level, suffered a moderate recession in the spring and early summer months and not until July did it rise. The recession was not apparent from the actual figures, which moved persistently upward; but this upward movement from March through June was in fact less than the usual seasonal advance, and our adjusted index therefore declined. The decline, though definite, was not extreme, and the index remained above normal throughout this period. In July, the increase in the actual figures was greater than usually occurs in that month, and resulted in the upturn referred to above.